DVM students report higher psychological distress than the Australian public, medical students, junior medical officers and practicing veterinarians. Issue 10 (16th July 2019) - Yang, HH; Ward, MP; Fawcett, A
Abstract : Aim: To measure the stress levels of Doctor of Veterinary Medicine (DVM) students at the University of Sydney using the Kessler Psychological Distress Scale (K10) questionnaire. Methods: DVM students in years 1 to 4 were surveyed in semester 2 of 2018. The voluntary online survey consisted of 6 demographic questions and the K10 scale, a standardised measure of stress commonly used in Australia by medical practitioners for evaluation and referral to mental health professionals. Academic year cohorts were compared to identify differences in stress levels. Cohorts were compared to published K10 scores from various populations including the Australian public, medical students, practicing veterinarians, and Junior Medical Officers (JMOs). Results: The response rate was 54.4% (n = 237). DVM students experienced a higher level of psychological distress (mean 24, median 23, range 10‐50) than the Australian population (mean 14.5, median 13, range 10‐50), medical students (mean 18.4, median 16, range 10‐50), practicing veterinarians (mean 16.7, median 15.5, range 10‐30), and JMOs (mean 18.1, median 16, range 10‐50). Female students (median 23) had a significantly higher level of psychological distress compared to male students (median 18) (p = 0.0005). International students (median 23) had a higher level of psychological stress than domestic students (median 22) (p = 0.0488). Different year cohorts, age range, work hours, and exercise were not associated with difference in stress levels. Conclusion: Based on higher levels of stress in DVM students than that of the general population, practicing veterinarians, JMOs and medical students, there is an urgent need for evidence‐based interventions to target stress in DVM students.